Can a point-of-decision-prompt intervention increase stair use? -- an analysis of a community intervention - Luchini, Alyson (My University, 2009)
This study was part of a large initiative known as Activate Fox Cities being undertaken in the Fox Cities, in Eastern Wisconsin. The purpose of this study was to assess reported stair use, reaction to the point-of-decision-prompts, perceived barriers, and in addition would provide recommendations regarding stair use at five Fox Cities locations through a survey format. This study was of importance due to two significant problems. First, there is a growing overweight and obesity epidemic in the United States, and the need for effective solutions to reduce chronic, lifestyle related disease and to increase physical activity rates. Secondly, according to the United Way Fox Cities, the 2006 Fox Cities Behavioral Risk Factor Surveillance System (BRFSS) showed that chronic diseases are the leading causes of death in the Fox Cities. A descriptive study was conducted using a survey format to collect data. A pre-intervention (n=503) and post-intervention (n=304) survey was administered, with collected data being statistically analyzed using descriptive and inferential statistics. The findings from this study indicated that a pointof- decision-prompt intervention could be effective in increasing stair use in the workplace. The data also provided insight into barriers toward stair use, reaction to pointof- decision-prompts, and effects of prompts on overall health with some significant data results being found.
Keywords: Stairs; Exercise -- Psychological aspects; Signs and signboards